Evaluation Of Maillard Reaction-Based Time-Temperature Integrator For The Assessment Of Thermal Impact On Quality Changes Of Thermally Processed Foods [TP372.55.M35 F686 2007 f rb]. - Foo, Wan Teck (2007)
Fenomenon kejatuhan nilai pH yang didorong oleh tindak balas Maillard sebagai asas pembinaan integrator masa-suhu (TTI) telah dikajisiasat.